The impact of micro credit on financial condition and socio-economic of women entrepreneurs in Bangladesh - Chowdhury, Mohammad Abdul Matin; Che Mohd Salleh, Marhanum (Global Academic Excellent, 2017)
Bangladesh is an innovator and home of abstracting micro credit program. It has taken few programs to alleviate poverty and enhance the quality of life among poor people. The main purpose of this research is to examine the impact of micro credit on financial condition as well as the socio-economic factors of women entrepreneurs in Bangladesh. Quantitative research method is adopted in this research to answer all the research objectives. Overall 230 women entrepreneurs have involved in the survey conducted in this research. Based on descriptive analyses, it is found that micro credit does not significantly affected the borrowers’ financial condition and some of the socio-economic variable including social security, health consciousness, entrepreneurship, and education. This research gives input to the micro finance institutions especially in Bangladesh to develop potential products to increase the borrowers’ financial and economic condition which at the same time alleviating poverty in the country. Finally, it is also benefits the Bangladesh government to enhance the existing policy on financial matters towards enhancing standard of living among the society in Bangladesh.